Is SDR Creation Inflationary?. (Policy Papers; Policy Paper ;, 2011)
Giving greater prominence to SDRs in international reserves would entail allocating them more frequently in significant amounts. The question has properly been raised whether such issuance would be inflationary for the world economy. This short paper addresses that question. It explores five different 'scenarios' that describe how recipient countries and the leading central banks-most notably the U.S. Federal Reserve (FRB) and the EU's European Central Bank (ECB)-would respond to those allocations. It concludes that SDR issuance would be inflationary for the world economy under two of the scenarios, but not under the remaining three scenarios, which include the most likely ones.